Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have the following limit:

$$ \lim_{x\to \infty}{\bigg( \frac{x^2 + 3x - 1}{x^2 + 3} \bigg) }^\frac{x -2}{2} $$ We had no explanations for calculating such limits i looked over few poor textbook examples and i understand the result of this limit will be $ e^X $ where X will be what i get from expanding the limits $ \frac {x-2}{2} $.

And that first step is to get the following form:
$$ \lim_{x\to\infty}{ \bigg ( 1 + \frac{1}{x+1} \bigg )^{x+1} } = e $$

Are there any simpler steps to solving such a limit ?

share|cite|improve this question
I have no idea what is going on in the second half. For the original expression, take the logarithm. You get a product where one factor goes to $1$ and the other to $\infty$ (colloquially, a $1\cdot\infty$ expression). Convert to a $0/0$ expression by moving one term into the denominator, and use L'Hôpital. (Sorry, no time for further explanations – family matters intervene – there is a big holiday ahead …) – Harald Hanche-Olsen Dec 23 '12 at 18:46
up vote 3 down vote accepted

$$\lim_{x\to \infty}{\left( \frac{x^2 + 3x - 1}{x^2 + 3} \right) }^\frac{x -2}{2}=\lim_{x\to \infty}{\left( \frac{x^2 + 3-3+3x - 1}{x^2 + 3} \right) }^\frac{x -2}{2}=\lim_{x\to \infty}{\left( \frac{x^2 + 3+3x - 4}{x^2 + 3} \right) }^\frac{x -2}{2}=\lim_{x\to \infty}{\left( 1+\frac{3x - 4}{x^2 + 3} \right) }^\frac{x -2}{2}=\lim_{x\to \infty}{\left( 1+\frac{3x - 4}{x^2 + 3} \right) }^{\frac{x^2+3}{3x-4}\cdot \frac{3x-4}{x^2+3}\cdot\frac{x -2}{2}}\overset{def}{=}L$$ Since exists $\lim\limits_{x\to \infty}{\left( \dfrac{3x-4}{x^2+3}\cdot\dfrac{x -2}{2} \right) }=\dfrac{3}{2}$, then $L=e^\frac{3}{2}.$

share|cite|improve this answer
Thanks mate you have no idea how much this helps. – Sterling Duchess Dec 23 '12 at 21:51

Another approach:

If $\lim\limits_{x\to{+\infty}} f(x)^{g(x)}$ is $1^{+\infty}$, which is an indeterminate form, then: $$\lim_{x\to{+\infty}} f(x)^{g(x)}=e^{\lim\limits_{x\to +\infty}\big(f(x)-1\big)g(x)}$$

share|cite|improve this answer
The more approaches, the better! – amWhy Mar 4 '13 at 0:43

You're right that you want to use the fact that $$\lim_{x\to\infty} f(x) = \lim_{x\to\infty} e^{F(x)},$$ where $F = \log f$. In this case, using L'hopital's rule, \begin{align*}\lim_{x\to\infty} \frac{x-2}{2} \log \left(\frac{x^2+3x-1}{x^2+3}\right) &= \lim_{x\to\infty} \frac{ \log \left(\frac{x^2+3x-1}{x^2+3}\right) }{\frac{2}{x-2}}\\ &= \lim_{x\to\infty} \frac{\frac{-3x^2+8x+9}{(x^2+3)(x^2+3x-1)}}{\frac{-2}{(x-2)^2}}\\ &= \lim_{x\to\infty} \frac{(x-2)^2(-3x^2+8x+9)}{-2(x^2+3)(x^2+3x-1)}\\ &= \frac{3}{2}, \end{align*} so your original limit is equal to $e^{3/2}.$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.